A basis for IgY-themed functional foods: Digestion profile of oral yolk immunoglobulin (IgY) by INFOGEST static digestion model. (December 2022) - Xia, Minquan; Ahn, Dong Uk; Liu, Cong; Cai, Zhaoxia
Graphical abstract: Highlights: Yolk immunoglobulin (IgY) digestion behavior and products are studied by simulation. IgY degrades easily in intestinal phase (89.49% digestibility) but not in gastric phase. IgY digestion involves aggregation, depolymerization and degradation into pieces. Over 6 peptides and 21 amino acids are detected, including 6 essential amino acids. IgY doesn't reach its maximum digestion degree at gastrointestinal digestion for 240 min. Abstract: Although yolk immunoglobulin (IgY) has been reported its functions of antiviral, antibacterial, energy balancing, and gut microbiota regulating, its gastrointestinal digestion process and the digestion products have not been studied, which is of great significance for the development of IgY-themed functional foods. This work investigated the digestion behaviors of oral IgY by static digestion simulation in vitro . IgY showed low digestibility (23.97%) in the gastric phase but was highly digestible (89.49% digestibility) in the initial intestinal phase. The entire digestion involved IgY aggregation, degradation, re-aggregation, and gradual decomposition into small pieces (by dynamic light scattering). These results indicated that IgY was impressionable, unstable and changeful in gastrointestinal environment, which might impair the bioactive function of IgY. Over 6 peptides (such as RGFK, TVPSGASTK, VPAATASPR) and 21 amino acids were detected, including 6 essential amino acids (methionine, isoleucine, leucine, histidine, tryptophan, and lysine), suggesting that IgY could be involved in human health regulation as active peptides or as rich sources of amino acids in addition to its own bioactive functions. The digestion kinetic curve confirmed that IgY did not reach its maximum digestion at the end of simulation of intestinal phase, implying the incomplete utilization of IgY. This study provides valuable details of oral IgY for development as active ingredients of a functional food, contributing to boosting the egg industry and improving human health.